Using the Results of a National Assessment of Educational Achievement - Kellaghan, Thomas (World Bank, 2012)
This book, the fifth and final volume of the National Assessments of Educational Achievement series, draws on the experiences of over forty countries that have implemented a national assessment. It considers the role of contextual factors which impinge on the use of assessment findings. The attachment of sanctions to performance on a national assessment and use of assessment results for accountability are discussed. Key components of a national assessment report are specified . Other instruments to communicate findings are described. Uses of national assessment findings for policy, management, teaching, and raising public awareness are described. A number of ways in which the use and value of national assessments could be optimized are proposed. This volume is intended primarily for teams who are responsible for conducting national assessments and policy makers responsible for the dissemination and use of national assessment results.